Gender Gap in Healthcare Worker—Patient Communication during the COVID-19 Pandemic: An Italian Observational Study - Vitale Elsa (Psych, 2022)
The value of the healthcare worker–patient communication has been well demonstrated and validated in several studies evidencing its relation to positive patient health outcomes, including better care response, simpler decision-making, better patient psychological well-being, and, therefore, considerable patient care satisfaction. The present study purposed to assess how patients perceived healthcare worker–patient communication during the COVID-19 pandemic and whether there were any gender-related differences among participants. From March 2020 to April 2020, an online questionnaire was administered to those who declared a patient’s condition in this period. The data considered included data on gender and a Quality of Communication questionnaire (QOC). A total of 120 patients were recruited online. Of these, 52 (43.33%) were females and 68 (56.67%) were males. Significant differences were recorded between females and males in the QOC questionnaire as regards Item no.2 (p = 0.033), Item no.6 (p = 0.007), Item no.11 (p = 0.013), Item no.12 (p = 0.003), Item no.13 (p = 0.002), Item no.15 (p = 0.008), and Item no.16 (p = 0.037), respectively. The potentially different elements between the two sexes considered were assessed in: Component 1: the need to be completely informed about their own health condition, and Component 2: the need to receive authentic and sincere communication from the healthcare worker involved. In light of the present findings, it has emerged that male patients seemed to be more active and positive in effective healthcare worker–patient communication.